Cost-effectiveness analysis of different devices used for the closure of small-to-medium-sized patent ductus arteriosus in pediatric patients - Sonia A El-Saiedi; Amal M El Sisi; Rodina Sobhy Mandour; Doaa M Abdel-Aziz; Wael A Attia (Wolters Kluwer Medknow Publications, 2017)
Aims: In this study, we examined the differences in cost and effectiveness of various devices used for the closure of small to medium sized patent ductus arteriosus (PDA). Setting and Design: We retrospectively studied 116 patients who underwent closure of small PDAs between January 2010 and January 2015. Subjects and Methods: Three types of devices were used: the Amplatzer duct occluder (ADO) II, the cook detachable coil and the Nit Occlud coil (NOC). Immediate and late complications were recorded and patients were followed up for 3 months after the procedure. Statistical Methods: All statistical calculations were performed using Statistical Package for the Social Science software. P <0.05 were considered significant. Results: We successfully deployed ADO II devices in 33 out of 35 cases, cook detachable coils in 36 out of 40 cases and NOCs in 38 out of 41 cases. In the remaining nine cases, the first device was unsuitable or embolized and required retrieval and replacement with another device. Eleven patients (9.5%) developed vascular complications and required anticoagulation therapy. Patients who had hemolysis or vascular complications remained longer in the intensive care unit, with consequently higher total cost (P = 0.016). Also, the need for a second device increased the cost per patient. Conclusions: The cook detachable coil is the most cost.effective device for closure of small.to medium.sized PDAs. Calculations of the incremental cost.effectiveness. (ICE) revealed that the Cook detachable coil had less ICE than the ADO II and NOC. The NOC was more effective with fewer complications.